Modulation of Hemostatic and Inflammatory Responses by Leptospira Spp. - Mônica L Vieira; Clément Naudin; Matthias Mörgelin; Eliete C Romero; Ana Lucia T O Nascimento; Heiko Herwald (Public Library of Science (PLoS), 2016)
Leptospirosis is a worldwide spread zoonotic and neglected infectious disease of human and veterinary concern that is caused by pathogenic Leptospira species. In severe infections, hemostatic impairments such as coagulation/fibrinolysis dysfunction are frequently observed. These complications often occur when the host response is controlled and/or modulated by the bacterial pathogen. In the present investigation, we aimed to analyze the modulation of the hemostatic and inflammatory host responses by the bacterial pathogen Leptospira. The effects of leptospires and their secreted products on stimulation of human intrinsic and extrinsic pathways of coagulation were investigated by means of altered clotting times, assembly and activation of contact system and induction of tissue factor. We show that both extrinsic and intrinsic coagulation cascades are modulated in response to Leptospira or leptospiral secreted proteins. We further find that the pro-inflammatory mediator bradykinin is released following contact activation at the bacterial surface and that pro-coagulant microvesicles are shed from monocytes in response to infection. Also, we show that human leptospirosis patients present higher levels of circulating pro-coagulant microvesicles than healthy individuals. Here we show that both pathways of the coagulation system are modulated by leptospires, possibly leading to altered hemostatic and inflammatory responses during the disease. Our results contribute to the understanding of the leptospirosis pathophysiological mechanisms and may open new routes for the discovery of novel treatments for the severe manifestations of the disease.